Leadership in the Management of the Director - Padilla, Omar (2023)
Nowadays, educational organizations, due to the great responsibility they have in the formation of human beings, face great changes and face innumerable challenges to provide high-level educational experiences and to ensure a relevant position in a challenging society. Therefore, the figure of the director is key because s/he is the natural leader of schools, and it is necessary to effectively and efficiently conduct school management. The present study intended to reveal the feeling of teachers of the San Juan de Miraflores district in Metropolitan Lima concerning the leadership in the director's management. It was research developed under a qualitative approach, which used the hermeneutical phenomenological method to interpret the interview made with four teachers from three private institutions of the San Juan de Miraflores district, who were selected meeting certain parameters. The findings allowed the definition of three key categories within the discourse of educators: the role of the director in schools, managerial leadership in educational management, and the importance of leadership in the director's management, which defined new research concerns.